E-Portfolio as an Evaluative Tool for Emergency Virtual Education: Analysis of the Case of the University Andres Bello (Chile) During the COVID-19 Pandemic - Rodriguez, Rubén; Martinez-Ulloa, Lorena; Flores-Bustos, Carolina (Frontiers in Psychology, 2022)
The confinement had serious implications for university education, specifically in the adaptation of face-to-face teaching to on-line methodologies. This article analyses the perception of speech therapy students from a Chilean University about the E-portfolio incorporation as an evaluative tool during the emergency virtual teaching due to COVID-19 pandemic. From quantitative research a survey of 38 questions based in Likert scales was applied to 108 students from fourth degree. The survey demonstrated that there is an improvement in methodology and teaching support, and as well as in the creativity and professionalism.